First Draft Genome Sequence of the Pathogenic Fungus Lomentospora prolificans (Formerly Scedosporium prolificans) - Ruibang Luo; Aleksey Zimin; Rachael Workman; Yunfan Fan; Geo Pertea; Nina Grossman; Maggie P. Wear; Bei Jia; Heather Miller; Arturo Casadevall; Winston Timp; Sean X. Zhang; et al. (G3: Genes, Genomes, Genetics, 2017)
Here we describe the sequencing and assembly of the pathogenic fungus Lomentospora prolificans using a combination of short, highly accurate Illumina reads and additional coverage in very long Oxford Nanopore reads. The resulting assembly is highly contiguous, containing a total of 37,627,092 bp with over 98% of the sequence in just 26 scaffolds. Annotation identified 8896 protein-coding genes. Pulsed-field gel analysis suggests that this organism contains at least 7 and possibly 11 chromosomes, the two longest of which have sizes corresponding closely to the sizes of the longest scaffolds, at 6.6 and 5.7 Mb.